A proposed model of motivational influences on academic achievement with flow as the mediator - Syed Mustafa, Sharifah Muzlia; Elias, Habibah; Mohd Noah, Sidek; Roslan, Samsilah (Elsevier, 2010)
Motivation is a combined force that influences students to work hard and achieve academically. However, there seem to be a missing link between motivation and academic achievement - learning engagement may be the answer. The aim of this paper is to propose the need for an integration of constructs from six different motivational theories into one motivational path, with flow as the mediator, in order to explain academic achievement better. When these motivational forces work together effectively, they are predicted to influence students to be in a state of flow – engagement in learning tasks. It is also predicted that being in a state of flow will contribute to high academic performance.